2019
DOI: 10.1021/acsanm.9b00956
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Numbers of Gold Nanoparticles in the Test Zone of Lateral Flow Immunoassay Strips

Abstract: Lateral flow immunoassay (LFIA) is a rapid and simple point-of-care method for the detection of various analytes. In the colorimetric sandwich format, the reaction outcome is a colored test zone line formed by Au nanoparticle (AuNP) conjugates captured by bound analyte molecules. Although nanoparticle design is crucial for the assay sensitivity, the correlation between the test zone brightness and the number and size of captured AuNPs has not been studied in detail. To fill this gap, we used an unprecedented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 33 publications
4
76
1
Order By: Relevance
“…The presented data differ with the earlier published [37] comparison of GNPs with Au cores and small CTAC shells that cover the diameter range from 16 to 115 nm with high homogeneity (RSD 2−3%). In the previous study, the monotonous dependence of LoD on the GNP diameter was found to reach 0.157 pg/mL of cTnI for the largest GNPs.…”
Section: Immunochromatographic Assay and Data Processingcontrasting
confidence: 99%
See 1 more Smart Citation
“…The presented data differ with the earlier published [37] comparison of GNPs with Au cores and small CTAC shells that cover the diameter range from 16 to 115 nm with high homogeneity (RSD 2−3%). In the previous study, the monotonous dependence of LoD on the GNP diameter was found to reach 0.157 pg/mL of cTnI for the largest GNPs.…”
Section: Immunochromatographic Assay and Data Processingcontrasting
confidence: 99%
“…Some experimental results show that 30-40 nm GNPs are optimal [17,35,36] because smaller particles have unacceptably small extinction cross-sections and small surface areas for antibody internalization. On the other hand, we recently demonstrated that increasing the nanoparticle size up to 115 nm reduced the LoD [37]. Moreover, conclusions about the capabilities of a label can be made only by comparing the analytical characteristics achieved for its conjugates with antibodies of different compositions [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…To meet both requirements, one needs a detection sensitivity of about 0.01 ng/L, which is higher than the reported SERS-based data. Recent analysis [ 11 ] showed that, in an ideal LFIA format, one analyte molecule delivers just one Au NP to the test zone. In this case, the theoretical LODs were in picograms per milliliter range for a typical LFIA format with 0.1 mL of a 25 kDa analyte.…”
Section: Sers Signal Accumulation and Data Processingmentioning
confidence: 99%
“…We recently estimated the required particle densities, depending on their size. So, for particles with a size of 16 nm, it is necessary that the biospecific reaction delivers at least 6.7 × 10 7 particles/mm 2 to the test zone [ 11 ]. This substantial surface density explains one of the first drawbacks of LFIA—low sensitivity relative to other immunological methods.…”
Section: Introductionmentioning
confidence: 99%
“…The number of gold nanoparticles per analyte capturing area might be the key of this enhanced detection. For AuNP*, the limit of detection was approximated to the particle diameter to the power of negative three (d -3 ), meaning the bigger AuNP* would result in less detection limit [12]. However, one analyte was captured by the limited number of AuNP*, so there was not much gold nanoparticles per area.…”
Section: Enhanced Detection Of Hbsabmentioning
confidence: 99%